Divide and rule: A qualitative analysis of the debriefing process in elite team sports - Macquet, A.-C.; Ferrand, C.; Stanton, N. A. (Applied Ergonomics, 2015)
This article aimed to gain an understanding of the process of debriefing during major competitions in elite team sports. Debrief interviews were conducted with 9 head coaches. The interview data were used to identify how head coaches divided up the tasks given to staff and team members prior to, and during the post-match debriefing. Results showed that debriefing consisted of two steps: preparation and presentation. Preparation referred to four successive tasks. Presentation to the team of players consisted of eight tasks relating to transformational and transactional styles of leadership. Coaches were shown to divide the labor within the staff and team. The data tend to support the view that in elite team sports, coaches are both transformational and transactional leaders, adapting their style of leadership to the situation, athletes and time available. This study provides insights into the task-work and team-work underlying team functioning and division of labor.